2014
DOI: 10.1007/s00442-014-3052-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monsoon precipitation variability on the physiological response of two dominant C4 grasses across a semiarid ecotone

Abstract: For the southwestern United States, climate models project an increase in extreme precipitation events and prolonged dry periods. While most studies emphasize plant functional type response to precipitation variability, it is also important to understand the physiological characteristics of dominant plant species that define plant community composition and, in part, regulate ecosystem response to climate change. We utilized rainout shelters to alter the magnitude and frequency of rainfall and measured the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…1; Thomey et al 2014). Organic matter content statistically differed during the experiment (p ¼ 0.0008, F 4,59 ¼ 5.57, r 2 ¼ 0.29; Table 1), specifically with regard to month (p ¼ 0.004, F 2,59 ¼ 6.10) and location (p ¼ 0.003, F 1,59 ¼ 9.43) but not rainfall treatment (p ¼ 0.4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1; Thomey et al 2014). Organic matter content statistically differed during the experiment (p ¼ 0.0008, F 4,59 ¼ 5.57, r 2 ¼ 0.29; Table 1), specifically with regard to month (p ¼ 0.004, F 2,59 ¼ 6.10) and location (p ¼ 0.003, F 1,59 ¼ 9.43) but not rainfall treatment (p ¼ 0.4).…”
Section: Resultsmentioning
confidence: 99%
“…Rain not only triggered microbial activity, but also presumably influenced nutrient availability via plant-microbe associations. Following the onset of monsoon watering, plants rapidly upregulated photosynthesis, peaking 4-5 days following a rain event (Thomey et al 2014), and likely exuded labile compounds through roots and plant residue (Geisseler et al 2011), which have been hypothesized to drive microbial activity in general (Fierer and Schimel 2003) and at our site (Vargas et al 2012). Likewise, increases in labile compounds and soil moisture can stimulate microbes to produce enzymes (Dorodnikov et al 2009, Gonzalez-Polo andAustin 2009), and enzyme activities increased shortly after early season rainfall.…”
Section: Discussionmentioning
confidence: 96%
“…Atmospheric nitrogen deposition is also increasing at the SNWR and regionally (Fenn et al 2003;Báez et al 2007). Furthermore, Thomey et al (2014) found that rates of leaf-level carbon fixation were higher in B. gracilis than in B. eriopoda after rainfall pulses under two different experimental precipitation regimes in plots where they co-occurred. Thus, by nearly all measures B. gracilis should be replacing B. eriopoda in this grassland, but the opposite is occurring (fig.…”
Section: Discussionmentioning
confidence: 97%
“…Species-specific responses in leaf-level photosynthesis to pulses and different rooting depths (two-layer hypothesis) are well documented but may not necessarily predict competitive outcomes nor explain patterns of dominance or changes in species composition. For example, Thomey et al (2014) showed that the photosynthetic response of B. gracilis to water pulses outperformed that of B. eriopoda, despite the fact that abundance of B. eriopoda is increasing faster than B. gracilis across a desert-grassland ecotone (Collins & Xia 2015). Mechanistic models that directly incorporate resource exchanges into competition coefficients could be developed to mechanistically link these two levels of the HPDF.…”
Section: Vascular Plant-plant Interactionsmentioning
confidence: 98%